2018
DOI: 10.1017/s1471068418000157
|View full text |Cite
|
Sign up to set email alerts
|

Solving Horn Clauses on Inductive Data Types Without Induction

Abstract: We address the problem of verifying the satisfiability of Constrained Horn Clauses (CHCs) based on theories of inductively defined data structures, such as lists and trees. We propose a transformation technique whose objective is the removal of these data structures from CHCs, hence reducing their satisfiability to a satisfiability problem for CHCs on integers and booleans. We propose a transformation algorithm and identify a class of clauses where it always succeeds. We also consider an extension of that algo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 36 publications
0
53
0
Order By: Relevance
“…Concerning the mechanization of our transformation technique, we need to extend the Elimination Algorithm [10] with a suitable automated mechanism for introducing difference predicates and/or auxiliary queries. As shown in Sections 3 and 4, this mechanism can be based on the result of matching the clauses obtained by unfolding (see clause 12 in the InsertionSort example, and clause 12 in the Rotate example) against the predicate definitions introduced in previous transformation steps (see clause 9 in both examples).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Concerning the mechanization of our transformation technique, we need to extend the Elimination Algorithm [10] with a suitable automated mechanism for introducing difference predicates and/or auxiliary queries. As shown in Sections 3 and 4, this mechanism can be based on the result of matching the clauses obtained by unfolding (see clause 12 in the InsertionSort example, and clause 12 in the Rotate example) against the predicate definitions introduced in previous transformation steps (see clause 9 in both examples).…”
Section: Discussionmentioning
confidence: 99%
“…However, proving the satisfiability of the clauses obtained by that translation is, in many cases, a much harder task. In a series of papers [5,7,8,9,10,16,19] it has been shown that by combining various transformation techniques, such as Specialization and Predicate Pairing, we can derive equisatisfiable sets of clauses where the efficacy of the CHC solvers is significantly improved. This approach avoids the burden of implementing very sophisticated solving strategies depending on the class of satisfiability problems to be solved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations